Doppler velocimetry in dichorionic twin pregnancies and its correlation with various fetal outcome - Satyabhuwan Singh Netam; Sanjay Kumar; Jamila Fani; Tripti Nagaria; Vivek Patre; Rajesh Singh; Vishal Jain (International Journal of Medical Research and Review, 2017)
Aim: This study was to evaluate the applicability of Doppler velocimetry to determine its correlation with fetal outcome in dichorionic twin pregnancies.Material and methods: Doppler examination of the umbilical artery (UA) and middle cerebral artery (MCA) was performed in 57 twin pairs. Abnormal values of the umbilical artery pulsatility index (PI), umbilical artery Resistive index (RI) were above the 95th percentile and below 5th percentile for the Middle cerebral artery pulsatility index (MCA PI) and Middle cerebral artery resistivity index (MCA RI) for gestational week. The difference of UA PI ≥0.5 in twin pairs was considered abnormal.Results: 33 subjects had a fetal discordance of greater than 15%. Birth weight was found to be significantly lower in subjects with Umbilical artery PI greater than 95th percentile for gestational age (p=0.014). Abnormal MCA RI (P=0.018) and Umbilical artery RI values above 95th percentile was significantly associated with increased risk of IUGR (intra uterine growth restriction) (P=0.036) and NICU (Neonatal intensive care unit) admission (P=0.005). Increased Umbilical artery PI values above 95th percentile was significantly associated with IUGR (P=0.003). Increased Umbilical Artery systolic/diastolic ratio above 95th percentile was significantly associated with IUGR (P=0.002), NICU admission (P=0.026) and still birth (P=0.026). Abnormal cerebra-umbilical ratio (<1.08) was significantly associated with IUGR (P=0.001) and still birth (P=0.025). Difference in pulsatility index of umbilical artery of both fetus (P1-P2 >0.5) was significantly correlated with increased degree of birth weight discordance of the twins, IUGR (P=0.001) and still birth (P=0.001).Conclusion: Abnormal Doppler values in discordant twin fetus are more likely to be associated with abnormal fetal outcome.